2021
DOI: 10.1177/0272989x211005655
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision Making Tools for People Facing Stroke Prevention Strategies in Atrial Fibrillation: A Systematic Review and Environmental Scan

Abstract: Objective Shared decision making (SDM) tools can help implement guideline recommendations for patients with atrial fibrillation (AF) considering stroke prevention strategies. We sought to characterize all available SDM tools for this purpose and examine their quality and clinical impact. Methods We searched through multiple bibliographic databases, social media, and an SDM tool repository from inception to May 2020 and contacted authors of identified SDM tools. Eligible tools had to offer information about war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The results align with published studies of SDM for stroke prevention in AF, some of which have been shown to produce small improvements in patient knowledge and reductions in decisional con ict [15][16][17] .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results align with published studies of SDM for stroke prevention in AF, some of which have been shown to produce small improvements in patient knowledge and reductions in decisional con ict [15][16][17] .…”
Section: Discussionsupporting
confidence: 85%
“…Tools for SDM should be feasible to implement in busy clinical practices 15 . In the current study, the SDM materials, which comprised a short presentation on AF and its diagnosis and treatment, were introduced in three tertiary medical centers in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…One review [44] met 15 of 16 AMSTAR2 domains, one [48] fully or partly met 14, and one [54] fully or partly met 13. Five reviews met just under half of their relevant criteria [51,57,58,61,62], and five reviews met just over half of their relevant criteria [47,50,60,63,64]. The remaining reviews met most of their relevant criteria.…”
Section: Self-monitoringmentioning
confidence: 99%
“…Interventions to improve adherence included the following: education and/or decision aids (four reviews) [44,55,62,64]; self-testing with clinician dosing or self-management with dosing according to rules (eight reviews) [38,44,46,48,53,54,61,63]; and pharmacist management (four reviews) [45,47,49,66]. The most common outcomes reported were TTR, proportion of INR measurements in range, or PDC (a measure used for direct OACs as they do not require as frequent blood monitoring as warfarin).…”
Section: Self-monitoringmentioning
confidence: 99%
“…However, although DOACs have been used widely since, there may still be an unmet barrier in clinical practice today with consequences for patient centred care (17).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%